Research on the Construction of Adherence and Its Influencing Factors of Patients with Percutaneous Coronary Intervention in Phase Ⅰ Cardiac Rehabilitation - CHEN Yilin, LIN Ping, HAN Yongkui, WANG Yini (Zhongguo quanke yixue, 2023)
Background The importance of phase Ⅰ cardiac rehabilitation after percutaneous coronary intervention (PCI) has been confirmed, but there is suboptimal adherence among patients. Therefore, investigating the adherence of PCI patients to phaseⅠ cardiac rehabilitation and the influencing factors can provide a theoretical foundation for improving the adherence of patients. Objective To clarifythe influencing factors of the adherence of PCI patients to phaseⅠ cardiac rehabilitation and the effect pathways by the structural equation model construction, in order to provide the oretical support for improving the adherence of PCI patients to phase Ⅰ cardiac rehabilitation. Methods Patients with PCI enrolled in the Cardiac Rehabilitation Center of the Second Hospital of Harbin Medical University from August to December in 2021 were selected as the research objects by convenience sampling. The general demographic information questionnaire, therapy adherence questionnaire, health belief of coronary heart disease questionnaire, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiexy Disorde-7 (GAD-7), Family Adaptability and Cohesion Evaluation Scale (FACES), Chronic Illness Resource Survey (CIRS), Gensini score were used to investigate the patients by the end of phaseⅠ cardiac rehabilitation. Spearman rank correlation analysis was used to verify the correlations between health belief, depression, anxiety, family adaptability and cohesion, chronic illness resource utilization and cardiac rehabilitation adherence, respectively. Based on correlation analysis, the hypothetical model of the influencing factors of the adherence of PCI patients to phaseⅠ cardiac rehabilitation was constructed combined with Anderson's model of health service utilization. Maximum likelihood method was used to fit and modify the model constantly. Structural equation model was used to analyze the relationship among influencing factors. Results A total of 443 questionnaires were distributed and 430 valid questionnaires were returned, with a valid return rate of 97.06%. The results of multiple linear regression analysis showed that health belief (β=0.427), depression (β=-0.057), anxiety (β=-0.130), family adaptability and cohesion (β=0.242), chronic illness resource (β=0.140) were independent factors of the adherence to phaseⅠcardiac rehabilitation of PCI patients (P<0.05). The results of the correlation analysis showed that cardiac rehabilitation adherence score of PCI patients was positively correlated with health beliefs, family adaptability and cohesion, chronic illness resource utilization (P<0.05) and negatively correlated with depression and anxiety (P<0.05). A structural equation model of the adherence of PCT patients to phaseⅠ cardiac rehabilitation was constructed using health belief, depression, anxiety, family adaptability and cohesion, chronic illness resource and the model fits well: χ2/df=3.092<5, standardized root mean square residual (SRMR) =0.070<0.080, goodness of fit indices (GFI) =0.981, adjusted goodness of fitindices (AGFI) =0.936, comparative fit index (CFI) =0.992, normed fit indexes (NFI) =0.989, with all of them>0.9. The results of the intermediate effects test showed that health belief, family adaptability and cohesion, chronic illness resource had positive direct effect on the adherence of PCI patients to phaseⅠ cardiac rehabilitation (β=0.395, 0.277, 0.152, P<0.01) ; health belief, family adaptability and cohesion had a positive indirect effect on the adherence of PCI patients to phaseⅠ cardiac rehabilitation through chronic disease resource utilization (β=0.057, 0.065, P<0.01). Depression and anxiety had a direct negative effect on the adherence of PCI patients to phaseⅠ cardiac rehabilitation (β=-0.055, -0.116, P<0.05) . Conclusion The adherence of PCI patients to phaseⅠ cardiac rehabilitation is influenced by multiple factors. There are complex pathway relationships among the influencing factors. Health belief, family adaptability and cohesion, chronic illness resource have a positive direct effect on the adherence of PCI patients to phaseⅠ cardiac rehabilitation; depression and anxiety have a negative direct effect on the adherence of PCI patients to phaseⅠ cardiac rehabilitation; health beliefs, family adaptability and cohesion have a positive indirect effect on the adherence of PCI patients to phaseⅠ cardiac rehabilitation through chronic illness resource utilization, and have a negative indirect effect on the adherence of PCI patients to phaseⅠ cardiac rehabilitation through anxiety and depression.